(untitled) (The Conference Hub, 2025)
This article describes how Kara amma from the work “Between Two Doors” thinks more about her child than herself in any situation, and that she is a true Uzbek woman. This work highlights the suffering of people from the famine, their work behind the front lines. The inner feelings of mothers who were burned by the loss of their children during World War II are expressed.